Strategi Peningkatan Kualitas Produk untuk Meningkatkan Jumlah Pelanggan dalam Studi Kasus Usaha Tahu Asri di Kec. Bonjol Kab. Pasaman - Intan Mutia; Rika Widianita (Lembaga Yasin AlSys, 2026)
Product quality in the tofu industry has been a concern in various studies, but research that specifically discusses strategies for improving product quality in traditional tofu businesses in relation to increasing the number of customers remains limited. This study aims to analyze product quality improvement strategies in increasing the number of customers at Usaha Tahu Asri in Bonjol Subdistrict, Pasaman Regency. This study employed a qualitative approach with a case study design, involving informants consisting of the business owner, workers, and consumers selected through purposive sampling. Data were collected through in-depth interviews, direct observation, and documentation, and were then analyzed using qualitative data analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results showed that product quality was not yet consistent, which was influenced by the use of non-standardized raw materials, production processes that were still manual without standard operating procedures, and quality control that was not yet systematic. In addition, limited product innovation and the low skill level of workers also affected product quality and the number of customers. These findings contribute to the development of studies on product quality and strategic management in the context of micro-enterprises based on traditional production, as well as broadening understanding of the importance of product quality in increasing the number of customers. The conclusion of this study affirms the importance of standardizing raw materials, production processes, quality control, and improving workers’ skills to enhance product quality and support business sustainability. The implications of this study include a theoretical contribution to the development of the MSME literature as well as practical implications for business actors in improving competitiveness.